2012
DOI: 10.1007/s11136-012-0206-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among adults with work-related asthma in the United States

Abstract: Purpose-The objective of this study was to examine health-related quality of life among adults with work-related asthma. Methods-We analyzed 2006-2009 Behavioral RiskFactor Surveillance System Asthma Callback Survey data for ever-employed adults with current asthma from 38 states and District of Columbia. Individuals with work-related asthma had been told by a doctor or other health professional that their asthma was related to any job they ever had. Health-related quality of life indicators included poor self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…These findings are consistent with our previous report that an estimated 62.8% of ever-employed adults with asthma in 38 states and District of Columbia are females. 11 In addition, although we found a higher proportion of asthma that is farm related for male operators than for female operators (16.9% versus 10.4%), this difference was not statistically significant. This was consistent with a report by Torén and Blanc where proportion of asthma that could be attributed to occupational exposures was 9.1% for males and 11.5% for females.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…These findings are consistent with our previous report that an estimated 62.8% of ever-employed adults with asthma in 38 states and District of Columbia are females. 11 In addition, although we found a higher proportion of asthma that is farm related for male operators than for female operators (16.9% versus 10.4%), this difference was not statistically significant. This was consistent with a report by Torén and Blanc where proportion of asthma that could be attributed to occupational exposures was 9.1% for males and 11.5% for females.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition to socioeconomic consequences, work-related asthma has been associated with disability, poor health-related quality of life, and mortality. 8,10,11 A review of population-based studies estimates that 7% to 51% (median 17.6%) of adult-onset asthma is attributable to occupational exposures such as vapors, gas, dust, and fumes. 12 Work-related asthma is associated with over 400 causative agents.…”
Section: Introductionmentioning
confidence: 99%
“…12 We previously reported that among adults with current asthma, 9% were diagnosed with WRA and an additional 38% describe their asthma as caused or worsened by workplace exposures (possible WRA). 13 Persons with WRA have lower SES and may have more severe disease than those with non-WRA. 1315 Therefore, persons with WRA may be at higher risk for severe asthma exacerbation associated with influenza virus infection than those with non-WRA.…”
Section: Introductionmentioning
confidence: 99%
“…12,15 A populationbased study found that employed adults with asthma and with work-related asthma exhibited a more impaired QoL than non-work-related patients with asthma. 16 The relationship between body mass index (BMI) and asthma incidence was demonstrated in a cohort study. 17 Results of a recent study in Taiwan indicated that low physical fitness and high sedentary time increased the central obesity risk, which led to asthma.…”
mentioning
confidence: 99%